Confocal laser scanning microscopy reveals species-specific differences in distribution of fluorescent proteins in coral tissues - Marchioro, Giulia M.; Coelho, David; Bouderlique, Thibault; Abed-Navandi, Daniel; Schagerl, Michael; D’Angelo, Cecilia; Kruckenhauser, Luise; Adameyko, Igor; Frade, Pedro R. (Frontiers in Marine Science, 2024)
Reef-building corals have a variety of green fluorescent protein (GFP)-like proteins, also known as fluorescent proteins (FPs). These proteins have broad spectral properties covering most of the visible spectrum, with fluorophores fluorescing from cyan to red. However, the role of FPs is still a topic of debate and requires further investigation, particularly in the direction of mapping these FPs within the coral tissue and describing their cell- and tissue-level distributions. This study applied confocal laser scanning microscopy (CLSM) to investigate species-specific differences in the distribution of FPs in three coral taxa (Stylophora sp., Acropora sp., Echinopora sp.), combined with their photoacclimation response and that of associated symbiotic algae to light gradients in a controlled aquarium experiment. CLSM produced high-resolution images that enabled the identification of different FPs, their tissue distribution and quantification of their fluorescence intensity, as well as quantification of symbiont chlorophyll a (chl-a) fluorescence. Emission scans revealed three emission peaks between 490 - 501 nm (cyan, CFPs), 510 - 515 nm (green, GFPs), and 679 nm (chl-a fluorescence signal; Fchl) shared by all three studied species. The distribution of GFPs in Stylophora was concentrated in the intermesenterial muscle bands of the polyp, whereas CFPs were typically located at the tips of the tentacles. In contrast, Acropora and Echinopora exhibited agglomeration of CFPs and GFPs primarily in the epidermis. In general, species-specific differences in FP distribution remained unaltered during the experiment. However, linear regression models showed a significant negative relationship between CFP fluorescence intensity and light irradiance in Stylophora, whereas Echinopora exhibited a negative relation between chlorophyll fluorescence (Fchl) and light. In summary, the CLSM methodology provided a high-resolution tool to study coral FP patterns and symbiont response to irradiance, revealing ecophysiological differences among coral species at the tissue and cellular levels. CLSM has the potential to elucidate the intricacies of coral photobiology within the natural environment and to discern their adaptive responses in situ.